2014
DOI: 10.3844/ajptsp.2014.75.83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dimethoate (An Organophosphate Insecticide) on the Reproductive System and Fertility of Adult Male Rat

Abstract: The pesticides are one of the most potentially harmful chemicals liberated in the environment in an unplanned manner. Dimethoate is widely used as a potent pesticide in many countries and has been shown to produce some adverse health effects. In the present study, we investigated the effect of dimethoate (an organophosphate insecticide) on the reproductive system and fertility of male rats and the possible mechanism underlining its action. Twenty four adult Wistar male rats were divided into 4 groups of 6 anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
37
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 34 publications
12
37
1
2
Order By: Relevance
“…The increase of cholesterol level in the testicular tissue may result from its non-utilization for production of testosterone. Similar observations were reported by Ngoula et al (2007) who tested pirimiphos-methyl, an organophosphorous pesticide in rats. In addition, Yamamoto et al (1999) have reported that high testicular cholesterol concentration have a detrimental effect on Leydig and Sertoli cell secretory function, spermatogenesis, epididymal sperm maturation process (decreased sperm motility and concentration), and the overall sperm fertilizing capacity.…”
Section: Discussionsupporting
confidence: 87%
“…The increase of cholesterol level in the testicular tissue may result from its non-utilization for production of testosterone. Similar observations were reported by Ngoula et al (2007) who tested pirimiphos-methyl, an organophosphorous pesticide in rats. In addition, Yamamoto et al (1999) have reported that high testicular cholesterol concentration have a detrimental effect on Leydig and Sertoli cell secretory function, spermatogenesis, epididymal sperm maturation process (decreased sperm motility and concentration), and the overall sperm fertilizing capacity.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, they are considered as risk factors of many diseases such as cancer, congenital malformations and infertility (Rudant et al, 2007). Pesticides damage reproduction of animals and some reported effects are the reduction in testosterone production and/or action (Bustos-Obregon and Gonzalez-Hormazabal, 2003) and the decrease in sperm count and mobility (Naravana et al, 2005;Ngoula et al, 2007;Kenfack et al, 2015;Nwozo et al, 2016). One of the mechanisms by which they perform their toxicity is the generation of high production of free radicals and then of the oxidative stress (Banerjee et al, 2001;Amin and Hashem, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Mating and fertility indices were reduced, in which one of the main causes for this could be the possible decrease in testosterone level together with unfavourable effects on libido (Farag et al, 2012). Decreasing in the relative weights of ventral prostate and testes, sperm motility and concentration, cholesterol and protein level in the serum and testes, the activity of prostatic acid phosphatase as well as fertility, gestation, litter size and parturition indices have been reported in rats treated with Dimethoate (Ngoula et al, 2014). Furthermore, there was study disclosed that exposure of rats to the subchronic administration of Methomyl magnificently decreased the fertility index, weight of testes and accessory organs, serum testosterone level as well as sperm count and motility.…”
Section: Endocrine Disruptionmentioning
confidence: 98%